2017
DOI: 10.3892/ol.2017.5915
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aloe-emodin-induced photodynamic activity on the apoptosis of human gastric cancer cells: A pilot study

Abstract: The aim of the present study was to explore the effect of aloe-emodin (AE)-induced photodynamic activity in human gastric cancer cells. AE was used as a photosensitizer to explore the effect of photodynamic therapy (PDT) in human gastric cancer cells (SGC-7901). An MTT assay was used to detect the effect of AE-induced PDT in optimal concentrations and illumination energy densities in human gastric cancer cells. Following AE-induced PDT, morphological changes of the cells and the rate of cell death were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Moreover, AE-PDT had marked inhibitory eff ect in vivo and extended the survival time of animals without notable side eff ects [45]. Similar fi ndings were observed in human gastric cancer SGC-7901 cells where the AE-induced PDT resulted in the activation of mitochondrial-dependent apoptosis [46]. Apoptosis is also the main outcome of AE-PDT of osteosarcoma MG63 cells.…”
Section: Aloe Emodin As a Sensitizer In Photodynamic Therapysupporting
confidence: 59%
“…Moreover, AE-PDT had marked inhibitory eff ect in vivo and extended the survival time of animals without notable side eff ects [45]. Similar fi ndings were observed in human gastric cancer SGC-7901 cells where the AE-induced PDT resulted in the activation of mitochondrial-dependent apoptosis [46]. Apoptosis is also the main outcome of AE-PDT of osteosarcoma MG63 cells.…”
Section: Aloe Emodin As a Sensitizer In Photodynamic Therapysupporting
confidence: 59%
“…Furthermore, it is interesting to note that A. arborescens has been proposed as a palliative therapy in patients with metastatic cancer even in co-administration with the conventional anticancer therapy [9]. In relation to this, the isolated compounds and in particular aloe-emodin have been evaluated in various types of human cancer cell lines where they showed antiproliferative activity [10,11,12]. This activity was also reported in vivo in various mouse models [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Emodin is one of the effective ingredients of the Chinese medicine rhubarb. It has been reported that emodin has a number of pharmacological effects, including antiviral, antibacterial, immunoregulatory and antioxidant functions ( 13 , 14 ). Studies have demonstrated that emodin is able to induce apoptosis via EMT suppression and caspase-dependent signaling ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%